Fayga Ostrower : quando a arte toca a teoria e a teoria toca a arte - Botelho, Claudia (2016)
This dissertation presents the work of Fayga Ostrower as an artist and theoretician, seeking to know his abstract graphic production and approaching his vision about art. Has is to investigate the possible relations or contradictions that may exist betwee